Teaching for the Two-Sided Mind - Linda Verlee Williams (U.S.A Simon & Schuster, 1983)
Recent research on the brain has revolutionized our concept of how we think. The two sides of the brain serve radically different functions. The left hemisphere is associated with linear, analytic thought; the right hemisphere governs spatial, integrative thought. In Teaching for the Two-Sided Mind Linda VerLee Williams explores the application of this important research to the classroom, summarizing current knowledge, discussing its implications, and providing practical teaching techniques that draw upon the right side of the brain. Students need right-brain strength to achieve balanced thinking skills and to activate a full range of cognitive and creative abilities. Right-brain techniques are remarkably effective in teaching children with learning disabilities and provide a valuable boost to gifted and average students. Specific classroom activities employing visual thinking, fantasy, metaphor, multisensory learning, music, laboratory experiments and field trips are described in Teaching for the Two-Sided Mind. The activities are suitable for classes from early elementary to high school level." Teachers, parents and all those interested in education will find Teaching for the Two-Sided Mind a fascinating exploration of how the most recent psychological findings can be put to use in the classroom.